2015
DOI: 10.1007/s12328-015-0619-2
|View full text |Cite
|
Sign up to set email alerts
|

A case of gastric adenocarcinoma of fundic gland type resected by combination of laparoscopic and endoscopic approaches to neoplasia with non-exposure technique (CLEAN-NET)

Abstract: A male in his eighties attended our hospital for further evaluation of gastric cancer. A gastroscopy revealed a whitish flat elevated lesion (Paris, 0-IIa) of 15 mm in diameter on the greater curvature of the proximal fornix. The preoperative diagnosis was intra-mucosal differentiated gastric cancer, and a novel therapeutic approach, combination of laparoscopic and endoscopic approaches to neoplasia with non-exposure technique (CLEAN-NET) was applied and the lesion was resected in a single piece without any co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 11 publications
0
19
0
1
Order By: Relevance
“…Comparison between standard gastrectomy with lymphadenectomy and function-preserving surgery with SNBD has been recently reported [27,28], although these studies did not include cases with these procedures. However, the feasibility of these procedures for gastric submucosal tumors and gastric cancer has been demonstrated previously [8,19,24,29]. SNNS-based function-preserving and limited surgery is expected to be more effective by using local resection techniques, such as these methods; however, there may be some technical limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison between standard gastrectomy with lymphadenectomy and function-preserving surgery with SNBD has been recently reported [27,28], although these studies did not include cases with these procedures. However, the feasibility of these procedures for gastric submucosal tumors and gastric cancer has been demonstrated previously [8,19,24,29]. SNNS-based function-preserving and limited surgery is expected to be more effective by using local resection techniques, such as these methods; however, there may be some technical limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Applying this guideline to reported GA-FG-CCPs, several cases did not meet curative criteria based on the depth of massive submucosal invasion. Considering the high frequency of submucosal invasion, Kato et al[15] suggested the efficacy of the combination of laparoscopic and endoscopic approaches to neoplasia with non-exposure technique (CLEAN-NET), a form of non-exposure laparoscopy and endoscopy cooperative surgery (LECS). CLEAN-NET may represent a therapeutic option for GA-FG-CCP because it facilitates easy resection of tumors located in the upper third of stomach, whereas ESD is technically challenging.…”
Section: Treatment and Prognosismentioning
confidence: 99%
“…Table 1 provides details of the previous 10 cases of gastric cancer that underwent LECS and our present case. [3][4][5][6] Of these 11 reports, eight cases were in men and three in women. The patients had a median age of 75 years (range, 66-91 years), and the median tumor size was 20 mm (range, 5-60 mm).…”
Section: Discussionmentioning
confidence: 99%